Optimizing three-dimensional (3D) map view on mobile devices as navigation aids using artificial neural network - Abubakar, Adamu; Zeki, Akram M.; Chiroma, Haruna (2013)
Prior research on real-world way-finding and environmental design principles has shown that effective virtual design supports skilled way-finding behaviour. Darken and Cevik [1] proved that augmentations such as direction indicators, maps and path restriction greatly improve way finding performance and achieve overall user satisfaction when represented in large-scale virtual structures. This study includes a control variable (screen size of a mobile device) that was not previously considered as a means in improving way finding given the increased use of 3D maps for mobile devices as navigation aids. A subjective experiment was carried out in order to determine the user preferences. The result indicated that the screen size of mobile devices suitable for navigation aid is directly related to the perceived effectiveness and that pictorially realistic satellite imagery that allows 3D view manipulation does not depend on screen size. Through an artificial neural network, the users' perception was compared to the screen size of mobile devices and the analysis showed that medium to large screen sized mobile devices are most commonly used for navigation and that the small screen of mobile devices was not affected by the presence or absence of 3D effects in monocular static displays.